The RNA methyltransferase Dnmt2 is required for efficient Dicer-2-dependent siRNA pathway activity in drosophila - Durdevic, Zeljko; Mobin, Mehrpouya Balaghy; Hanna, Katharina; Lyko, Frank; Schaefer, Matthias R. (Cell reports, 2013)
Transfer RNA (tRNA) fragmentation in response to stress conditions has been described in many organisms. tRNA fragments have been found in association with small interfering RNA (siRNA) components, but the biological role of these interactions remains unclear. We report here that the tRNA methyltransferase Dnmt2 is essential for efficient Dicer-2 (Dcr-2) function in Drosophila. Using small RNA (sRNA) sequencing, we confirmed that Dnmt2 limits the extent of tRNA fragmentation during the heat-shock response. tRNAs as well as tRNA fragments serve as Dcr-2 substrates, and Dcr-2 degrades tRNA-derived sequences, especially under heat-shock conditions. tRNA-derived RNAs are able to inhibit Dcr-2 activity on long double-stranded RNAs (dsRNAs). Consequently, heat-shocked Dnmt2 mutant animals accumulate dsRNAs, produce fewer siRNAs, and show misregulation of siRNA pathway-dependent genes. These results reveal the impact of tRNA fragmentation on siRNA pathways and implicate tRNA modifications in the regulation of sRNA homeostasis during the heat-shock response.
Gesehen am 05.01.2021